Bovine streptococcal mastitis in Southwest and Northern States of Nigeria. (2010)
An investigation was carried out to identify the streptococci species isolated from clinical cases of bovine mastitis in Kwara, Kaduna and Oyo States of Nigeria. Milk samples from 200 clinically mastitic udders were bacteriological studied. A total of 130 streptococci isolate belonging to six species of streptococci, namely S. uberis, S. agalactiae, S. dysgalactiae, S. epidemicus, S. bovis, S. equinus were recovered from the milk examined. Streptococcus uberis was the most frequently encountered species with an incidence of (55.4%) followed by Streptococcus agalactiae (24.6%), Streptococcus dysgalactiae (12.3%) Streptococcus zoopidemicus (3.9%) Streptococcus bovis (2.3%) and Streptococcus equinus (1.5%). These species of streptococcus are of great public importance.